Produção, caracterização e propriedades de superfície de filmes finos de Ti-Nb-Zr - Costa, Sidney Cherman Zolabarrieta (2023)
With the increasing use of implants, due to the possibility of replacing certain parts of the human body as a means to improve health, there is a growing body of research on biocompatible metallic alloys. One widely used alloy is Ti-6Al-4V; however, aluminum ions can cause disturbances in the nervous system, and vanadium ions can be cytotoxic. Due to these issues, the search for new alloys has brought about various possibilities, such as Ti-β alloys, which exhibit properties close to human bone and their structure can exhibit stable or metastable phases, depending on the alloying elements, such as Nb, which has an effect on the stability of the beta phase and mechanical strength. The magnetron sputtering process is a widely used technique for depositing thin films, as it offers high deposition rates, low working pressures, and control over the surface quality of the deposited film. This study used this technique to produce thin films of the TiNbZr alloy on AISI 316L steel for the evaluation of chemical and microstructural properties. Three compositions (% at) were produced: Ti66Nb21Zr13, Ti62Nb20Zr18, and Ti59Nb19Zr22. All samples exhibited the formation of the β-Ti phase and nano-scale structures. The Ti62Nb20Zr18 and Ti59Nb19Zr22 samples showed electrochemical behavior similar to that of Grade IV Ti and hold promise for use as coatings for 316L steel implants.